Analisis Mantan Narapidana Korupsi Menjadi Calon Legislatif Berdasarkan Prinsip Musawa dan Keadilan - Setiowati, Sulis; Umardani, Achmad (Manabia: Journal of Constitutional Law, 2024)
This research delves into the legal implications of Constitutional Court Decision No. 91/PUU- XVIII/2020, focusing on its impact on the inconsistency of Law Number 11 of 2020 and the resulting legal effects. Employing a juridical normative approach, the study examines legal concepts, principles, and regulations. The findings reveal that the Constitutional Court's conditional declaration of unconstitutionality for Law Number 11 of 2020 stems from discrepancies in its formation concerning clarity of purpose, formulation, and transparency, as stipulated by Law Number 12 of 2011 on the Formation of Legislation. The legal effects of Decision No. 91/PUU-XVIII/2020 on Law Number 11 of 2020 within Indonesia's legal system are significant. During the two-year rectification period, it retains legal status and is recorded in the Official Gazette. If no rectification occurs within two years, Law Number 11 of 2020 becomes permanently unconstitutional, and the prior laws it amended or replaced are reinstated. In conclusion, several recommendations are made: The Constitutional Court should issue clear, unambiguous verdicts for legal certainty. The public and academia should monitor government and legislative activities to uphold constitutional principles. This research sheds light on the legal implications of Constitutional Court Decision No. 91/PUU-XVIII/2020 and provides valuable guidance for Indonesia's legal and legislative stakeholders. The problem of political rights owned by former convicts arose after the enactment of PKPU No. 10 of 2023 and PKPU No. 11 of 2023 which determined that former convicts who would run for legislative candidates did not need to pass a five-year interval if they had received an additional sentence in the form of revocation of political rights. Whereas the Constitutional Court Decision No. 87/PUU-XX/2022 and Constitutional Court Decision No. 12/PUU-XXI/2023 determine that ex-convicts must pass a five-year interval, without any additional conditions. This study aims to determine the regulation of the political rights of former corruption convicts in legislative elections and to review analyze the perspective of the principles of musawa and justice on the regulation of former corruption convicts to become legislative candidates. This research uses normative legal research methods. the data used in this research uses secondary data literature legal materials. The data collected in this study were collected through documentation techniques. Based on the results of the research, it can be stated that the regulation of the political rights of former prisoners to become legislative candidates has experienced the dynamics of regulatory changes through the Election Law, Constitutional Court Decisions, Supreme Court Decisions and KPU Regulations. Supreme Court Decision No. 28 P / HUM / 2023, Constitutional Court Decision No. 87 / PUU-XX / 2022 and Constitutional Court Decision No. 12 / PUU-XXI / 2023 are in accordance with the principle of musawa in general because they have equalized the political rights of ex-corruption convicts just like other citizens.